As constituições estaduais e a educação ambiental : implicações para as políticas públicas educacionais - Campos, Adelina Neres de Sousa (2020)
The consolidation process of environmental education in Brazil, while important social field, is presenting itself more intense in the last years, emphasizing the need to surround the tenets of different subjects, such as environmental education. Thus, the general objective of this study was to analyze the conception of environment expressed in states constitutions and its implications while drafting educational public policies. As methodology a bibliographical and documental analysis research was performed, bringing about the reality of state constitutions regarding environmental education. This study reveals that environmental education is cited in the Federal Constitution of 1998 only once, in the specific chapter about the environment, which goes to the fact that this important subject was not highlighted by Brazilian Law, state Laws in all regions of Brazil also approach environmental education lightly, being that the states of Tocantins and Sergipe do not even address the issue of environmental education. When addressing specific educational Laws that cover educational law, the present study aimed to bring what is found in specific educational statutes (PCNs, DCNs, DCNEA and BNCC), considering the advancement and stagnation of educational laws that though are the basis in which a society is constructed, able of preserving the environment, still has timid actions in this regard. Finally, it was considered that in a reductionist style the BNCC addressed the environmental education without generating significative advancements which enabled a wider and more effective education by overcoming its demands. It was thus concluded, that environmental education is treated as a transversal subject in Brazilian schools, not getting the importance needed thought the environment contemplates the own existence of humanity, and, in this regard, must be relevantly and specifically addressed, in such way where it is possible to awaken in citizens the conscience that it is necessary to protect the environment and, to this end it is needed that each citizen is aware of its effective relationship with nature and, on this regard, that public policies address the subject of environmental education with the prominence that the subject demands, therefore, there must be no superficiality in the public policies that concern environmental issues.